Universality in the Neutron– 19 C Scattering Using Finite-Range Separable Interactions - Shalchi, M. A. [UNESP]; Yamashita, M. T. [UNESP]; Hadizadeh, M. R.; Frederico, T.; Tomio, Lauro [UNESP] (Springer Nature, 2017)
We report a study on the low-energy properties of the elastic s-wave scattering of a neutron (n) in the carbon isotope 19C near the critical condition for the occurrence of an excited Efimov state in the three-body n–n–18C system. For the separation energy of the two halo neutrons in 20C we use the available experimental data. We also investigate to which extent the universal scaling laws, strictly valid in the zero-range limit, will survive when using finite-range interactions. By allowing to vary the n–18C binding energy, a scaling behavior for the real and imaginary parts of the s-wave phase-shift δ0 is verified, emerging some universal characteristics given by the pole-position of kcot(δ0R) and effective-range parameters.